Bank Rakyat forges cooperation to promote education Financing-I - Siti Nur Azwin, Zulkapri (2018)
KUALA LUMPUR, July 9 (Bernama) - Bank Rakyat signed a Memorandum of Understanding (MoU) with Universiti Malaysia Pahang (UMP), AKATI Consulting (M) Sdn Bhd, Admal Aviation College and Kolej Poly-Tech MARA (KPTM) for prospective students to finance their higher education studies.